Sulforaphane’s Multifaceted Potential: From Neuroprotection to Anticancer Action - Raymond A. Otoo; Antiño R. Allen (Molecules, 2023)
Sulforaphane (SFN) is a naturally occurring compound found in cruciferous vegetables such as broccoli and cauliflower. It has been widely studied for its potential as a neuroprotective and anticancer agent. This review aims to critically evaluate the current evidence supporting the neuroprotective and anticancer effects of SFN and the potential mechanisms through which it exerts these effects. SFN has been shown to exert neuroprotective effects through the activation of the Nrf2 pathway, the modulation of neuroinflammation, and epigenetic mechanisms. In cancer treatment, SFN has demonstrated the ability to selectively induce cell death in cancer cells, inhibit histone deacetylase, and sensitize cancer cells to chemotherapy. SFN has also shown chemoprotective properties through inhibiting phase I metabolizing enzymes, modulating phase II xenobiotic-metabolizing enzymes, and targeting cancer stem cells. In addition to its potential as a therapeutic agent for neurological disorders and cancer treatment, SFN has shown promise as a potential treatment for cerebral ischemic injury and intracranial hemorrhage. Finally, the ongoing and completed clinical trials on SFN suggest potential therapeutic benefits, but more research is needed to establish its effectiveness. Overall, SFN holds significant promise as a natural compound with diverse therapeutic applications.